ChemInform Abstract: The Planar CoB18‐ Cluster as a Motif for Metallo‐Borophenes. Issue 35 (August 2016) - Li, Wan‐Lu; Jian, Tian; Chen, Xin; Chen, Teng‐Teng; Lopez, Gary V.; Li, Jun; Wang, Lai‐Sheng
Abstract: The title cluster is produced by laser vaporization of a boron/cobalt composite target and characterized by PES and quantum chemical CCSD(T) and DFT calculations.